Can Reducing Implant Costs Increase Revenue for Surgically Treated Ankle Fractures: Time Driven Activity Based Costing for 1 year Episode of Care. Issue 4 (22nd October 2020) - Freking, Will; Okelana, Bandele; McMillan, Logan J.; Kibble, Kendra; Parikh, Harsh R.; Cunningham, Brian P.
Category: Ankle; Trauma; Other Introduction/Purpose: Implant selection may provide an opportunity to reduce costs and improve value in healthcare, but most orthopaedic surgeons are unfamiliar with the cost of surgical implants. Large variation has been reported in the overall cost of the surgical treatment of ankle fractures, largely due to variations in implant selection. The purpose of this study is to evaluate the relationship between implant selection and the Reimbursed Cost of Care (RCC) over the total cost-of-care over the entire care episode. Methods: A single payer database was queried for isolated ankle fractures from 2010-2017. Patient characteristics, implant cost, RCC and total cost of care for one-year episodes were collected. Total cost of care was determined via Time Driven Activity Based Costing (TDABC). Analysis consisted of multivariable linear regression and goodness-of-fit tests. The relative proportion of the implant cost to the RCC was defined as Ic/RCC. Results: Construct costs (Inpatient: 1563.30 vs Outpatient: 1143.00; p<0.01)TDABC cost of care (Inpatient: 3670.90 vs Outpatient: 2941.90; p<0.01)RCC (Inpatient: 17350.00 vs Outpatient: 10895.80; p<0.01) were all significantly lower for the outpatient setting. Construct costs constituted an estimated 38.8% of the total TDABC cost and 14.5% of the RCC. The difference between RCC and implant costs presented a significant negative trend with the total construct costs for outpatient procedures (B=-1.54; p=0.03), but non-significant for inpatient (B=-0.37;p=0.79). Conclusion: This study investigated the effect of implant cost on the total cost of care in surgically treated ankle fractures. We found an overall higher reimbursed cost of care (RCC) in the outpatient setting and a higher TDABC cost of care in the inpatient setting, reinforcing the trend towards outpatient surgical management. Implant selection proved not only a significant portion of the overall cost of care, but a driver of overall revenue.